Anti-glare film
By setting specific optical properties and structures on the anti-glare layer of the anti-glare film, combining phase separation method and particle dispersion method, the problem of glare and anti-glare reduction caused by the installation of the anti-glare film on the display surface is solved, and efficient Light scattering and clear display.
Patent Information
- Application Number
- CN202111658768.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2017-08-04
- Filing Date
- 2018-06-25
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2038-06-25
AI Technical Summary
When installing an anti-glare film on the display surface, although external light can be prevented, it is easy to cause a decrease in display performance, especially on high-fine pixel displays, which may cause glaring and blurring of images, and reduce the concave and convex structure to reduce the Glamorousness will affect anti-glare properties.
By setting values with a glare value of less than 10, a mirror gloss of less than 40%, and a transmission image clarity of less than 40% on the anti-glare layer of the anti-glare film, the matrix resin and The refractive index difference and weight ratio of the particles form an appropriate concave and convex structure to suppress glare and improve anti-glare properties.
It realizes that while maintaining high anti-glare properties, it effectively suppresses the glare and image blur of the display, ensuring the clarity of the display effect.
Smart Images

Figure CN114265135B_ABST
Abstract
Description
[0001] This application is a divisional application based on a patent application with an application date of June 25, 2018, a priority date of August 4, 2017, an application number of 201880045262.6 (international application number PCT / JP2018 / 023952), and an invention name of “Anti-glare film”. Technical Field
[0002] The present invention relates to an anti-glare film for preventing external light from being reflected onto a display surface. Background Art
[0003] The anti-glare film is, for example, a film having a roughened surface to form projections and depressions, and is attached to the surface of a display to scatter external light and prevent the external light from being reflected into the display.
[0004] As methods for forming projections and depressions on the surface of an anti-glare film, for example, there are: a method of dispersing particles (fillers) in a matrix resin as disclosed in Patent Document 1 (hereinafter referred to as a particle dispersion method); a method of utilizing a phase separation structure formed by spinodal decomposition of liquid phases of multiple polymers as disclosed in Patent Document 2 (hereinafter referred to as a phase separation method); a method of transfer molding a projection and depression shape using a mold as disclosed in Patent Document 3 (hereinafter referred to as a transfer molding method), etc.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2009-109702
[0008] Patent Document 2: Japanese Patent No. 3559505
[0009] Patent Document 3: Japanese Patent Application Publication No. 2014-102356
[0010] Patent Document 4: Japanese Patent Application No. 2012-231496 Summary of the invention
[0011] Problems to be solved by the invention
[0012] When an anti-glare film is attached to the surface of a display, it is possible to prevent external light from being reflected into the display. However, on the other hand, the display performance of the display through the anti-glare film may be degraded.
[0013] In particular, if an anti-glare film is installed on the surface of a display having high-definition pixels, the light from the display that passes through the anti-glare film is refracted due to the surface unevenness of the anti-glare film, or the pixels of the display are magnified due to the lens effect caused by the surface unevenness of the anti-glare film, which causes glare and makes it difficult to observe the image.
[0014] As a method of suppressing the glare of the display, for example, reducing the surface irregularities of the anti-glare film may be considered. However, if the surface irregularities of the anti-glare film are reduced, there is a possibility that the anti-glare property may be reduced.
[0015] Therefore, an object of the present invention is to provide an anti-glare film which can appropriately suppress the glare of a display and has a good anti-glare property.
[0016] Solutions to the problem
[0017] An anti-glare film according to one embodiment of the present invention is an anti-glare film installed on the surface of a display, wherein the anti-glare film has an anti-glare layer, a glare value of the anti-glare layer specified based on the value of the standard deviation of the brightness distribution of the above-mentioned display when installed on the above-mentioned surface of the above-mentioned display is a value in the range of 10 or less, a specular gloss of the anti-glare layer measured at 60 degrees specular gloss is a value in the range of 40% or less, and a transmission image clarity of the anti-glare layer at a light comb width of 0.5 mm is set to a value in the range of 40% or less.
[0018] Here, the glare value is an objective index that can quantitatively evaluate the glare of a display. Specifically, the glare value is a value defined based on the standard deviation of the brightness distribution of the display, and indicates the degree of irregularity of bright spots on the display.
[0019] The transmission clarity is a value related to the quality of the anti-glare property, and the smaller the transmission clarity, the higher the anti-glare property.
[0020] As for the above-mentioned glare value, specular glossiness and transmission image clarity, for example, when the anti-glare layer is formed by a phase separation method, it can be achieved by adjusting the type of phase separation material combined, or the heating temperature of the composition in the drying process, the air volume of the dry air blown to the composition, or the linear speed, etc. in its manufacturing process. In addition, for example, when the anti-glare layer is formed by a particle dispersion method, it can be achieved by adjusting the difference between the refractive index of the matrix resin and the refractive index of multiple particles dispersed in the matrix resin to a given range in its manufacturing process. In addition, in order to make the difference in the refractive index between the matrix resin and the particles reach a given range, a material that can reach a given refractive index difference is selected as the material used for both, or the shape, number, density of the particles contained in the matrix resin, etc. are adjusted. In addition, the value of the ratio G2 / G1 of the weight G1 of the matrix resin and the total weight G2 of the multiple particles is adjusted.
[0021] According to the above configuration, the glare value of the anti-glare layer is set to a value in the range of 10 or less, and therefore, it can be set so that glare can be effectively suppressed based on quantitative evaluation.
[0022] The anti-glare layer is set to a value such that the clarity of the transmitted image is 40% or less. Thus, the anti-glare layer can obtain high anti-glare properties regardless of the haze value, which is another indicator of the quality of the anti-glare properties.
[0023] Furthermore, since the specular glossiness measured at 60 degrees is set to a value in the range of 40% or less, reflection of external light can be suppressed.
[0024] Therefore, the anti-glare film according to one embodiment of the present invention can appropriately suppress the glare of the display and exhibit good anti-glare properties.
[0025] In addition, the anti-glare film according to one embodiment of the present invention may have the following configuration: in the above configuration, the anti-glare layer includes a plurality of resin components and has a co-continuous phase structure formed by phase separation of the plurality of resin components.
[0026] In addition, the anti-glare film of a certain embodiment of the present invention can be configured as follows: in the above configuration, the anti-glare layer includes a matrix resin and a plurality of microparticles dispersed in the matrix resin, and the difference in refractive index between the microparticles and the matrix resin is a value in the range of greater than 0 and less than 0.07.
[0027] As described above, by setting the difference in refractive index between the matrix resin and the fine particles within a given range and dispersing a plurality of fine particles in the matrix resin, it is possible to appropriately suppress the glare of the display and to provide a good anti-glare property.
[0028] In addition, the anti-glare film of a certain embodiment of the present invention can be configured as follows: in the above configuration, the ratio G2 / G1 of the weight G1 of the above-mentioned base resin of the above-mentioned anti-glare layer to the total weight G2 of the above-mentioned multiple fine particles contained in the above-mentioned anti-glare layer is a value in the range of greater than 0.03 and less than 0.20.
[0029] Thereby, an antiglare film having an antiglare layer having a structure in which a plurality of fine particles are dispersed in a matrix resin can be produced favorably.
[0030] Effects of the Invention
[0031] The present invention is configured as described above, and the anti-glare film can appropriately suppress the glare of the display and has a good anti-glare property. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1It is a cross-sectional view showing the structure of the anti-glare film according to the embodiment of the present invention.
[0033] Figure 2 It is a figure which shows the manufacturing method of the anti-glare film which concerns on 3rd Embodiment.
[0034] Figure 3 This is a diagram showing an example of a schematic configuration of a glare evaluation device according to an embodiment of the present invention.
[0035] Explanation of symbols
[0036] 1 Anti-glare film
[0037] 3 Anti-glare layer
[0038] 16a Display DETAILED DESCRIPTION
[0039] Embodiments of the present invention will be described with reference to the drawings. Figure 1 1 is a cross-sectional view showing the structure of the anti-glare film 1 according to the embodiment of the present invention. The anti-glare film 1 is mounted on a display device 16 (see Figure 3 ) on the surface of the display 16a. The anti-glare film 1 includes a base film 2, an anti-glare layer 3, and an adhesive layer 4.
[0040] The base film 2 is disposed between the surface of the display 16a and the antiglare layer 3 to support the antiglare layer 3. The adhesive layer 4 is disposed between the surface of the display 16a and the base film 2 to fix the antiglare film 1 to the surface of the display 16a.
[0041] The anti-glare layer 3 is formed on at least one side of the substrate film 2. The anti-glare layer 3 imparts anti-glare properties to the anti-glare film 1, scatters and reflects external light, and prevents external light from being reflected into the display 16a. The anti-glare layer 3 also functions as a hard coating (HC) layer covering the surface of the substrate film 2. As an example, the anti-glare layer 3 includes a plurality of resin components that can undergo phase separation.
[0042] The anti-glare layer 3 is set so that the glare value is within a range of 10 or less. It should be noted that the glare value is defined based on the value of the standard deviation of the brightness distribution of the display 16a when the anti-glare film 1 is attached to the surface of the display 16a. The glare value can be obtained using a glare inspection machine 10 described later.
[0043] The antiglare layer 3 is set so that the transmission image clarity (image clarity) at a comb width of 0.5 mm is 40% or less. The transmission image clarity is a measure for quantifying blur and distortion of light passing through the antiglare layer 3 and is a value measured by a measurement method based on JIS K7105.
[0044] In addition, the specular gloss (60 degree gloss) of the anti-glare layer 3 measured at 60 degree specular gloss is set to a value within a range of 20% or less. Specular gloss is generally referred to as glossiness, which is a value indicating the degree of specular reflection light on the surface of an object, and is a value measured based on JIS K7136. It should be noted that the range of values that the haze value of the anti-glare layer 3 can take is not particularly limited.
[0045] Thus, the anti-glare film 1 of the present embodiment adopts a glare value that can objectively and quantitatively evaluate glare, and is designed so that the glare value is a value within a range of 10 or less. Therefore, compared with a case where the design is performed based on a value indicating the degree of glare by subjective evaluation, glare can be stably suppressed within a desired range.
[0046] In addition, the transmission clarity can be suppressed to a value in the range of 40% or less. Thus, the anti-glare layer 3 can obtain high anti-glare properties regardless of the haze value which is another index related to the quality of the anti-glare properties.
[0047] Furthermore, since the specular glossiness (60 degree glossiness) of the antiglare layer 3 measured at 60 degree specular glossiness is set to a value in the range of 40% or less, reflection of light onto the surface of the display 16 a can be suppressed.
[0048] The adhesive layer 4 is disposed between the surface of the display 16 a and the base film 2 , and fixes the anti-glare film 1 to the surface of the display 16 a .
[0049] Hereinafter, specific examples of the substrate film 2 and the anti-glare layer 3 are described. Among them, the anti-glare layer 3 formed by the phase separation method is described as the anti-glare layer 3 of the first embodiment, the anti-glare layer 3 formed by the particle dispersion method is described as the anti-glare layer 3 of the second embodiment, and the anti-glare layer 3 formed by the transfer molding method is described as the anti-glare layer 3 of the third embodiment.
[0050] [Base film]
[0051] Examples of the material of the base film 2 include glass, ceramics, and resins. As the resin, the same resin as the material of the antiglare layer 3 can be used. Preferred materials for the substrate film 2 include transparent polymers, such as cellulose derivatives (cellulose acetate such as triacetate (TAC) and cellulose diacetate), polyester resins (polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), polyarylate resins, etc.), polysulfone resins (polysulfone, polyethersulfone (PES), etc.), polyetherketone resins (polyetherketone (PEK), polyetheretherketone (PEEK), etc.), polycarbonate resins (PC), polyolefin resins (polyethylene, polypropylene, etc.), cyclic polyolefin resins (films manufactured by JSR Corporation [ARTON] (registered trademark), films manufactured by Zeon Corporation [ZEONEX] (registered trademark)), halogen-containing resins (polyvinylidene chloride, etc.), (meth) acrylic resins, styrene resins (polystyrene, etc.), vinyl acetate or vinyl alcohol resins (polyvinyl alcohol, etc.).
[0052] The base film 2 may be uniaxially or biaxially stretched, but is preferably an optically isotropic film with a low refractive index. Examples of the optically isotropic base film 2 include unstretched films.
[0053] The thickness of the base film 2 can be appropriately set, and is, for example, preferably 5 μm to 2000 μm, more preferably 15 μm to 1000 μm, and still more preferably 20 μm to 500 μm.
[0054] (First embodiment)
[0055] [Structure of Anti-glare Layer of First Embodiment]
[0056] The anti-glare layer 3 of the first embodiment has a phase separation structure of multiple resin components. As an example, the anti-glare layer 3 of the first embodiment has a structure in which multiple elongated (rope-like or line-like) protrusions are formed on the surface through the phase separation structure of multiple resin components. The elongated protrusions are branched to form a co-continuous phase structure in a dense state.
[0057] The anti-glare layer 3 of the first embodiment exhibits anti-glare properties by means of a plurality of elongated convex portions and concave portions located between adjacent elongated convex portions. The anti-glare film 1 is a film having an excellent balance between haze value and clarity of transmitted image by means of such an anti-glare layer 3. The surface of the anti-glare layer 3 of the first embodiment has a reticular structure, i.e., a plurality of continuous or partially missing irregular ring structures, because the elongated convex portions are formed into a roughly reticular shape.
[0058] By forming such a structure in the anti-glare layer 3 of the first embodiment, it is possible to prevent the formation of lens-shaped (island-shaped) convex parts in the anti-glare layer 3. As a result, it is possible to prevent the light from the display 16a passing through the anti-glare layer 3 of the first embodiment from being refracted due to the surface unevenness of the anti-glare layer 3, or the pixels of the display 16a from being magnified and observed due to the lens effect caused by the surface unevenness of the anti-glare layer 3, thereby suppressing the glare of the display 16a. As a result, even if the anti-glare film 1 is installed on the display 16a with high-definition pixels, it is possible to highly suppress glare while ensuring anti-glare properties, and it is also possible to suppress blurring of text, etc.
[0059] It should be noted that the plurality of elongated convex portions may be independent of each other or connected together. The phase separation structure of the anti-glare layer 3 of the first embodiment is as follows, and can be formed by spinodal decomposition (wet spinodal decomposition) from a liquid phase using a solution that is a raw material of the anti-glare layer 3. For details of the anti-glare layer 3 of the first embodiment, for example, reference can be made to the description of Patent Document 4.
[0060] [Material of the Anti-glare Layer in the First Embodiment]
[0061] The plurality of resin components contained in the antiglare layer 3 of the first embodiment may be any resin capable of phase separation. From the viewpoint of obtaining an antiglare layer 3 having elongated convex portions and high scratch resistance, the plurality of resin components contained in the antiglare layer 3 preferably include a polymer and a curable resin.
[0062] As the polymer contained in the anti-glare layer 3 of the first embodiment, for example, thermoplastic resins can be cited. As thermoplastic resins, for example, styrene resins, (meth) acrylic resins, organic acid vinyl ester resins, vinyl ether resins, halogen-containing resins, olefin resins (including alicyclic olefin resins), polycarbonate resins, polyester resins, polyamide resins, thermoplastic polyurethane resins, polysulfone resins (polyethersulfone, polysulfone, etc.), polyphenylene ether resins (polymers of 2,6-xylenol, etc.), cellulose derivatives (cellulose esters, cellulose carbamates, cellulose ethers, etc.), silicone resins (polydimethylsiloxane, polymethylphenylsiloxane, etc.), and rubber or elastomers (polybutadiene, polyisoprene and other diene rubbers, styrene-butadiene copolymers, acrylonitrile-butadiene copolymers, acrylic rubbers, polyurethane rubbers, silicone rubbers, etc.) can be cited. These thermoplastic resins can be used alone or in combination of two or more.
[0063] In addition, the polymer may include a material having a functional group that participates in a curing reaction or a functional group that reacts with a curable compound. The polymer may have a functional group in a main chain or a side chain.
[0064] Examples of the functional group include condensable groups, reactive groups (e.g., hydroxyl groups, acid anhydride groups, carboxyl groups, amino groups, imino groups, epoxy groups, glycidyl groups, isocyanate groups, etc.), and polymerizable groups (e.g., vinyl groups, propenyl groups, isopropenyl groups, butenyl groups, allyl groups, etc.). 2-6 Alkenyl, ethynyl, propynyl, butynyl, etc. 2-6 Alkynyl, vinylidene, etc. 2-6 Alkenylene, and groups having these polymerizable groups ((meth)acryloyl group, etc.) etc. Among these functional groups, polymerizable groups are preferred.
[0065] In addition, the anti-glare layer 3 of the first embodiment may also include a plurality of types of polymers. Each of the above-mentioned polymers may be phase-separated by spinodal decomposition from the liquid phase, or may be mutually incompatible. The combination of the first polymer and the second polymer included in the plurality of types of polymers is not particularly limited, and substances that are mutually incompatible near the processing temperature may be used.
[0066] For example, when the first polymer is a styrene resin (polystyrene, styrene-acrylonitrile copolymer, etc.), the second polymer may be a cellulose derivative (for example, cellulose esters such as cellulose acetate propionate), a (meth) acrylic resin (polymethyl methacrylate, etc.), an alicyclic olefin resin (a polymer containing norbornene as a monomer, etc.), a polycarbonate resin, and a polyester resin (polyC 2-4 Alkylene aromatic ester copolyesters, etc.
[0067] In addition, when the first polymer is a cellulose derivative (for example, cellulose esters such as cellulose acetate propionate), the second polymer may be a styrene resin (polystyrene, styrene-acrylonitrile copolymer, etc.), a (meth) acrylic resin, an alicyclic olefin resin (a polymer containing norbornene as a monomer, etc.), a polycarbonate resin, and a polyester resin (polyC 2-4 Alkylene aromatic ester copolyesters, etc.
[0068] The plurality of types of polymers may include at least cellulose esters (e.g., cellulose diacetate, cellulose triacetate, cellulose acetate propionate, cellulose acetate butyrate, etc.) 2-4 Alkyl carboxylates).
[0069] Here, the phase separation structure of the anti-glare layer 3 of the first embodiment can be fixed by curing the precursor of the curable resin contained in the various resin components by active energy rays (ultraviolet rays, electron beams, etc.) or heat when manufacturing the anti-glare layer 3. In addition, the anti-glare layer 3 of the first embodiment can be given scratch resistance and durability by such a curable resin.
[0070] From the viewpoint of obtaining scratch resistance, at least one polymer included in the plurality of types of polymers is preferably a polymer having a functional group that can react with a curable resin precursor in a side chain. As a polymer forming a phase separation structure, in addition to the two mutually incompatible polymers, a thermoplastic resin or other polymers may also be included. The mass ratio M1 / M2 of the mass M1 of the first polymer to the mass M2 of the second polymer, and the glass transition temperature of the polymer may be appropriately set.
[0071] Examples of curable resin precursors include curable compounds having functional groups that react with active energy rays (ultraviolet rays, electron beams, etc.) or heat, and that can be cured or crosslinked by the functional groups to form resins (particularly cured resins or crosslinked resins).
[0072] Examples of such compounds include thermosetting compounds or thermosetting resins (low molecular weight compounds having epoxy groups, polymerizable groups, isocyanate groups, alkoxysilyl groups, and silanol groups (e.g., epoxy resins, unsaturated polyester resins, urethane resins, silicone resins, etc.)), or photocurable (ionizing radiation curable) compounds that are cured by ultraviolet rays or electron beams (ultraviolet curable compounds such as photocurable monomers and oligomers, etc.).
[0073] As a preferred curable resin precursor, there can be mentioned photocurable compounds that cure in a short time due to ultraviolet rays or electron beams. Among them, ultraviolet curable compounds are particularly practical. In order to improve resistance such as scratch resistance, the photocurable compound preferably has more than 2 (preferably 2 to 15, and more preferably about 4 to 10) polymerizable unsaturated bonds in the molecule. Specifically, the photocurable compound is preferably epoxy (meth) acrylate, urethane (meth) acrylate, polyester (meth) acrylate, siloxane (meth) acrylate, and a multifunctional monomer having at least 2 polymerizable unsaturated bonds.
[0074] The curable resin precursor may also contain a curing agent corresponding to its type. For example, a thermosetting resin precursor may contain a curing agent such as an amine or a polycarboxylic acid, and a photopolymerization initiator may be contained in a photocurable resin precursor. As the photopolymerization initiator, conventional components such as acetophenones or propiophenones, benzyls, benzoins, benzophenones, thioxanthones, and acylphosphine oxides may be cited.
[0075] Furthermore, the curable resin precursor may contain a curing accelerator. For example, the photocurable resin precursor may contain a photocuring accelerator such as a tertiary amine (dialkylaminobenzoic acid ester, etc.) and a phosphine-based photopolymerization accelerator.
[0076] In the manufacturing process of the anti-glare layer 3 of the first embodiment, at least two components of the polymer and the curable resin precursor contained in the solution that will become the raw material of the anti-glare layer 3 are used in a combination that phase separates from each other near the processing temperature. As a combination that causes phase separation, for example, there can be mentioned: (a) a combination in which multiple types of polymers are incompatible with each other and phase separation occurs; (b) a combination in which a polymer and a curable resin precursor are incompatible and phase separation occurs; (c) a combination in which multiple types of curable resin precursors are incompatible with each other and phase separation occurs, etc. Among these combinations, generally, there can be mentioned (a) a combination of multiple types of polymers or (b) a combination of a polymer and a curable resin precursor, and (a) a combination of multiple types of polymers is particularly preferred.
[0077] Here, usually, the polymer and the cured resin or cross-linked resin generated by curing the curable resin precursor have different refractive indices. In addition, usually, the refractive indices of multiple types of polymers (the first polymer and the second polymer) are also different from each other. The difference in refractive index between the polymer and the cured resin or cross-linked resin, and the difference in refractive index between multiple types of polymers (the first polymer and the second polymer) are preferably a value in the range of 0 or more and 0.2 or less, and more preferably a value in the range of 0 or more and 0.07 or less.
[0078] In addition, the anti-glare layer 3 may include a plurality of fine particles (fillers) dispersed in the matrix resin. The fine particles may be any of organic fine particles and inorganic fine particles, and the plurality of fine particles may include fine particles of a plurality of types.
[0079] As organic particles, cross-linked acrylic particles and cross-linked styrene particles can be cited. In addition, as inorganic particles, silicon dioxide particles and aluminum oxide particles can be cited. In addition, as an example, the difference in refractive index between the particles contained in the anti-glare layer 3 and the matrix resin can be set to a value in the range of 0 or more and 0.2 or less. The difference in refractive index is preferably a value in the range of 0 or more and 0.15 or less, and more preferably a value in the range of 0 or more and 0.07 or less.
[0080] The average particle size of the fine particles is not particularly limited, and can be, for example, 0.5 μm to 5.0 μm. The average particle size is preferably 0.5 μm to 4.0 μm, and more preferably 1.0 μm to 3.0 μm.
[0081] It should be noted that the so-called average particle size here is the 50% volume average particle size in the Coulter counter method (the same applies to the average particle size described below). The particles can be solid or hollow. If the average particle size of the particles is too small, it is difficult to obtain anti-glare properties. If it is too large, there is a hidden danger of increased glare on the display, so it is necessary to pay attention.
[0082] The thickness of the anti-glare layer 3 of the first embodiment can be appropriately set, for example, preferably a value in the range of 0.3 μm to 20 μm, more preferably a value in the range of 1 μm to 15 μm, and further preferably a value in the range of 1 μm to 10 μm. Usually, it can be set to a value in the range of 2 μm to 10 μm (particularly a value in the range of 3 μm to 7 μm).
[0083] The antiglare film may be formed without the base film 2 . In this case, the thickness of the antiglare layer 3 is preferably, for example, 1 μm to 100 μm, more preferably 3 μm to 50 μm.
[0084] The anti-glare layer 3 of the first embodiment may contain conventional additives, such as organic or inorganic particles, stabilizers (antioxidants, ultraviolet absorbers, etc.), surfactants, water-soluble polymers, fillers, cross-linking agents, coupling agents, colorants, flame retardants, lubricants, waxes, preservatives, viscosity adjusters, tackifiers, leveling agents and defoaming agents, etc., within a range that does not impair the optical properties.
[0085] As for the manufacturing method of the anti-glare film 1 of the first embodiment, as an example, it includes the following steps: a preparation step of preparing a solution (hereinafter, also referred to as the solution) which is the raw material of the anti-glare layer 3 of the first embodiment; a formation step of applying the solution prepared in the preparation step to the surface of a given support (in the first embodiment, the base film 2), evaporating the solvent in the solution, and forming a phase separation structure by spinodal decomposition from the liquid phase; and a curing step of curing the curable resin precursor after the formation step.
[0086] [Preparation process]
[0087] In the preparation step, a solution containing a solvent and a resin composition for constituting the anti-glare layer 3 of the first embodiment is prepared. The solvent can be selected according to the type and solubility of the polymer and curable resin precursor contained in the anti-glare layer 3. The solvent can be a solvent that can at least uniformly dissolve the solid components (multiple types of polymers and curable resin precursors, reaction initiators, and other additives).
[0088] Examples of the solvent include ketones (acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc.), ethers (dimethyl The solvent may be selected from the group consisting of alkylene, tetrahydrofuran, etc., aliphatic hydrocarbons (hexane, etc.), alicyclic hydrocarbons (cyclohexane, etc.), aromatic hydrocarbons (toluene, xylene, etc.), halogenated carbons (methylene chloride, ethylene dichloride, etc.), esters (methyl acetate, ethyl acetate, butyl acetate, etc.), water, alcohols (ethanol, isopropanol, butanol, cyclohexanol, etc.), cellosolves (methyl cellosolve, ethyl cellosolve, etc.), cellosolve acetates, sulfoxides (dimethyl sulfoxide, etc.), and amides (dimethylformamide, dimethylacetamide, etc.). In addition, the solvent may be a mixed solvent.
[0089] As the resin composition, preferably, a thermoplastic resin, a photocurable compound, a photopolymerization initiator, and a composition comprising a thermoplastic resin and a photocurable compound are used. Alternatively, as the resin composition, preferably, a composition comprising a plurality of mutually incompatible polymers, a photocurable compound, and a photopolymerization initiator is used.
[0090] The concentration of the solute (polymer and curable resin precursor, reaction initiator, and other additives) in the mixed solution can be adjusted within a range where phase separation of the plurality of resin components occurs and within a range where castability and coating properties are not impaired.
[0091] [Formation process]
[0092] In the forming process, the solution prepared in the preparation process is cast or coated on the surface of the support (here, as an example, the substrate film 2). As the casting method or coating method of the solution, conventional methods can be cited, for example: a spray coater, a spin coater, a roll coater, an air knife coater, a blade coater, a rod coater, a reverse coater, a wire rod coater, a notch wheel coater, a dip coater, an immersion extrusion coater, a die coater, a gravure coater, a micro gravure coater, and a screen coater.
[0093] The solvent is evaporated and removed from the solution cast or coated on the surface of the support by drying. As the solution is concentrated during the evaporation process, phase separation occurs due to spinodal decomposition of various resin components from the liquid phase, forming a phase separation structure with a relatively regular interphase distance (pitch or mesh diameter). The co-continuous phase structure of the elongated convex portions can be produced by setting drying conditions and ratios that can improve the melt fluidity of the resin components after the solvent is evaporated to a certain extent.
[0094] As for the evaporation of the solvent, it is preferably carried out by heat drying from the viewpoint of facilitating the formation of the elongated convex portions on the surface of the anti-glare layer 3 of the first embodiment. If the drying temperature is too low or the drying time is too short, there is a risk that insufficient heat is applied to the resin component, the melt fluidity of the resin component is reduced, and the formation of the elongated convex portions becomes difficult, so it is necessary to pay attention.
[0095] On the other hand, if the drying temperature is too high or the drying time is too long, the temporarily formed elongated protrusions may flow and reduce their height, but their structure is maintained. Therefore, the glare value, mirror glossiness, transmission image clarity and haze value of the anti-glare layer 3 can be set to values within the range that can meet the above conditions. Therefore, in addition to adjusting the combination of phase separation materials, the height of the elongated protrusions can be adjusted by adjusting the drying temperature and the drying time. In addition, in the formation process, a co-continuous phase structure in which the phase separation structure is connected can be produced by increasing the evaporation temperature of the solvent or using a low-viscosity component in the resin component.
[0096] When a co-continuous phase structure is formed and coarsened as phase separation due to spinodal decomposition of multiple resin components from the liquid phase proceeds, the continuous phase becomes discontinuous and forms a droplet phase structure (an island structure of independent phases such as spheres, true spheres, disks, and ellipsoids). Here, depending on the degree of phase separation, an intermediate structure between the co-continuous phase structure and the droplet phase structure (a phase structure in the process of transition from the co-continuous phase to the droplet phase) may also be formed. After the solvent is removed, a layer with fine concavoconvexities on the surface is formed.
[0097] [Curing process]
[0098] In the curing step, the curable resin precursor contained in the solution is cured, thereby fixing the phase separation structure formed in the forming step to form the anti-glare layer 3 of the first embodiment. The curing of the curable resin precursor can be carried out by heating or irradiation with active energy rays, or a combination of these methods, depending on the type of the curable resin precursor. The active energy rays to be irradiated are selected according to the type of photocurable components, etc.
[0099] The irradiation of active energy rays can be carried out in an inert gas atmosphere as required. When the active energy rays are ultraviolet rays, as the light source, there can be used: a far ultraviolet lamp, a low-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a halogen lamp, and a laser light source (a light source such as a helium-cadmium laser and an excimer laser).
[0100] When forming the adhesive layer 4 , after preparing a solution containing an adhesive component, the solution can be applied and dried on the other side of the base film 2 by a conventional method such as the casting method or coating method described in the forming step.
[0101] By going through the above steps, the anti-glare film 1 of the first embodiment can be manufactured. It should be noted that, when a peelable support is used as the support, by peeling the anti-glare layer 3 from the support, an anti-glare film consisting only of the anti-glare layer 3 can be obtained. In addition, when a non-peelable support (preferably a transparent support such as a substrate film 2) is used as the support, an anti-glare film 1 having a laminated structure of a support (substrate film 2) and an anti-glare layer 3 can be obtained.
[0102] Here, as a method for suppressing the glare of the display 16a, for example, reducing the surface unevenness of the anti-glare layer can be considered, but there is a risk of reducing the anti-glare property of the anti-glare film. However, by not only reducing the unevenness of the anti-glare layer, but also increasing the number of unevenness while increasing the inclination of the unevenness of the anti-glare layer to make the unevenness steeper, the anti-glare property can be improved while suppressing the glare of the display.
[0103] In the first embodiment, such concavities and convexities can be formed in the anti-glare layer by the above-mentioned spinodal decomposition, and such concavities and convexities can also be formed in the anti-glare layer by other methods. For example, in the case where a plurality of particles are used to form the surface concavities and convexities of the anti-glare layer as described in the second embodiment, by selecting materials in a manner that the repulsive interaction between the particles and the resin and solvent other than the particles is enhanced when the anti-glare layer is formed, it is possible to cause appropriate aggregation of the particles and form a steep and high-density concavity and convexity distribution structure in the anti-glare layer. Therefore, the anti-glare layer of other embodiments is described below with the difference from the first embodiment as the center.
[0104] Hereinafter, the anti-glare layer 3 according to other embodiments (the second embodiment and the third embodiment) will be described.
[0105] (Second embodiment)
[0106] The anti-glare layer 3 of the second embodiment comprises a matrix resin and a plurality of microparticles dispersed in the matrix resin. The plurality of microparticles can be formed into a true sphere, but are not limited thereto, and can also be formed into a substantial spherical shape or an ellipsoidal shape. In addition, the microparticles can be formed into a solid shape or a hollow shape. When the microparticles are formed into a hollow shape, the hollow part of the microparticles can be filled with air or other gases. In the anti-glare layer 3 of the second embodiment, each microparticle can be dispersed in the form of a primary particle, or can be dispersed with a plurality of secondary particles formed by agglomeration of a plurality of microparticles.
[0107] The difference in refractive index between the matrix resin and the fine particles is set to a value in the range of 0 to 0.2. The difference in refractive index is more preferably a value in the range of 0 to 0.15, and more preferably a value in the range of 0 to 0.07.
[0108] The average particle size of the fine particles is set to a value in the range of 0.5 μm to 5.0 μm. The average particle size of the fine particles is more preferably a value in the range of 0.5 μm to 4.0 μm, and more preferably a value in the range of 1.0 μm to 3.0 μm.
[0109] For example, in the particle size distribution of the particles contained in the antiglare layer 3 , the average particle size of 50% by weight or more of the particles contained in the antiglare layer 3 is preferably controlled to have a deviation of within 1.0 μm.
[0110] Thus, fine particles having a relatively uniform particle size and an average particle size set within the above range can form uniform and appropriate irregularities on the surface of the anti-glare layer 3. This can suppress the glare of the display 16a while ensuring the anti-glare property.
[0111] In addition, the ratio of the weight of the matrix resin in the anti-glare layer 3 to the total weight of the plurality of microparticles can be appropriately set. In the second embodiment, the ratio G2 / G1 of the weight G1 of the matrix resin of the anti-glare layer 3 to the total weight G2 of the plurality of microparticles contained in the anti-glare layer 3 is set to a value in the range of 0.03 to 0.20. The ratio G2 / G1 is preferably a value in the range of 0.03 to 0.17, and more preferably a value in the range of 0.03 to 0.14.
[0112] The microparticles dispersed in the matrix resin may be any inorganic or organic microparticles, preferably having good transparency. As organic microparticles, plastic beads may be mentioned. As plastic beads, styrene beads (refractive index 1.59), melamine beads (refractive index 1.57), acrylic beads (refractive index 1.49), acrylic-styrene beads (refractive index 1.54), polycarbonate beads, polyethylene beads, etc. may be mentioned. The plastic beads preferably have a hydrophobic group on the surface. As such plastic beads, styrene beads may be mentioned.
[0113] Examples of the matrix resin include at least one of a photocurable resin that is cured by active energy rays, a solvent-drying resin that is cured by drying a solvent added during coating, and a thermosetting resin.
[0114] Examples of the photocurable resin include resins having acrylate functional groups, such as relatively low molecular weight polyester resins, polyether resins, acrylic resins, epoxy resins, urethane resins, alkyd resins, spiroacetal resins, polybutadiene resins, polythiol polyene resins, oligomers, prepolymers, and reactive diluents of (meth)acrylates of multifunctional compounds such as polyols.
[0115] Specific examples thereof include monofunctional monomers such as ethyl (meth)acrylate, ethylhexyl (meth)acrylate, styrene, methylstyrene, and N-vinyl pyrrolidone, and polyfunctional monomers such as polymethylolpropane tri(meth)acrylate, hexanediol (meth)acrylate, tripropylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and neopentyl glycol di(meth)acrylate.
[0116] When the photocurable resin is an ultraviolet curable resin, it is preferred to use a photopolymerization initiator. Examples of the photopolymerization initiator include acetophenones, benzophenones, Michlerbenzoylbenzoate, α-amyl oxime esters, tetramethylthiuram monosulfide, and thioxanthones. In addition, it is also preferred to mix a photosensitizer with the photocurable resin. Examples of the photosensitizer include n-butylamine, triethylamine, and poly-n-butylphosphine.
[0117] As the solvent drying type resin, known thermoplastic resins can be cited. As the thermoplastic resin, styrene resins, (meth) acrylic resins, vinyl acetate resins, vinyl ether resins, halogen-containing resins, alicyclic olefin resins, polycarbonate resins, polyester resins, polyamide resins, cellulose derivatives, silicone resins, and rubber or elastomers can be cited. As the solvent drying type resin, a resin soluble in an organic solvent is preferred, and a resin soluble in an organic solvent and having excellent formability, film forming properties, transparency and weather resistance is particularly preferred. As such a solvent drying type resin, styrene resins, (meth) acrylic resins, alicyclic olefin resins, polyester resins, cellulose derivatives (cellulose esters, etc.) can be cited.
[0118] Here, when the material of the substrate film 2 is a cellulose resin such as triacetyl cellulose (TAC), a cellulose resin can be cited as a thermoplastic resin used in the solvent drying type resin. The cellulose resin can be cited as a cellulose derivative such as nitrocellulose, cellulose acetate, butyl cellulose acetate, ethyl cellulose, methyl cellulose, cellulose acetate propionate, and ethyl hydroxyethyl cellulose. By using a cellulose resin as the solvent drying type resin, the substrate film 2 and the anti-glare layer 3 can be well adhered, and at the same time, excellent transparency can be obtained in the anti-glare film 1.
[0119] Examples of the solvent drying type resin include vinyl resins, acetal resins, acrylic resins, polystyrene resins, polyamide resins, and polycarbonate resins.
[0120] Examples of the thermosetting resin include phenolic resins, urea-formaldehyde resins, diallyl phthalate resins, melamine resins, guanamine resins, unsaturated polyester resins, polyurethane resins, epoxy resins, aminoalkyd resins, melamine-urea co-condensation resins, silicone resins, polysiloxane resins, etc. When a thermosetting resin is used as the base resin, at least any one of a crosslinking agent, a curing agent such as a polymerization initiator, a polymerization accelerator, a solvent, and a viscosity modifier may be used in combination.
[0121] As an example, the manufacturing method of the anti-glare film 1 of the second embodiment includes the following steps: a preparation step of preparing a solution that serves as a raw material for the anti-glare layer 3 of the second embodiment; a coating step of applying the solution prepared in the preparation step onto the surface of a given support (the substrate film 2 in the second embodiment); and a curing step of curing the resin in the coated solution.
[0122] [Preparation process]
[0123] In the preparation process, a solution containing a solvent and a resin composition and microparticles for constituting the anti-glare layer of the second embodiment is prepared. As the solvent, at least one of alcohols (isopropyl alcohol, methanol, ethanol, etc.), ketones (methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), cyclohexanone, etc.), esters (methyl acetate, ethyl acetate, butyl acetate, etc.), halogenated hydrocarbons, and aromatic hydrocarbons (toluene, xylene, etc.) can be cited. A known leveling agent can be further added to the solution. For example, by using a fluorine-based or silicone-based leveling agent, the anti-glare layer can be given good scratch resistance.
[0124] [Coating / curing process]
[0125] In the coating step, the solution prepared in the preparation step is cast or coated on the surface of a support (here, as an example, the base film 2) by the same method as in the first embodiment. The solvent is evaporated and removed from the solution cast or coated on the surface of the support by drying.
[0126] When the matrix resin is a photocurable resin, after the coating process, a curing process based on ultraviolet rays or electron beams is performed as an example. As the ultraviolet light source, various mercury lamps, ultraviolet carbon arc lamps, black light lamps, and metal halide lamps can be cited. In addition, as the wavelength range of ultraviolet rays, for example, a wavelength range of 190nm to 380nm can be cited.
[0127] In addition, the electron beam source may be a known electron beam accelerator, specifically, various electron beam accelerators such as the Van de Graaff type, Cocklof-Walton type, resonance transformer type, insulating core transformer type, linear type, high frequency high voltage (Dynamitron) type, and high frequency type.
[0128] By curing the matrix resin contained in the solution, the positions of the microparticles in the matrix resin can be fixed, thereby forming an anti-glare layer having a plurality of microparticles dispersed in the matrix resin and having a concavo-convex structure formed on the surface due to the microparticles.
[0129] According to the anti-glare film 1 of the second embodiment, by setting the difference in refractive index between the matrix resin and the fine particles within a predetermined range and dispersing a plurality of fine particles in the matrix resin, it is possible to ensure good anti-glare properties and suppress glare of the display 16 a .
[0130] (Third embodiment)
[0131] The anti-glare layer 3 of the anti-glare film 1 of the third embodiment has a structure in which a concavo-convex shape is formed on the surface on the side opposite to the substrate film 2. The anti-glare layer 3 of the third embodiment is composed of a resin layer. As an example, the resin layer is formed of the same material as the base resin contained in the anti-glare layer 3 of the second embodiment.
[0132] As an example, the antiglare film 1 of the third embodiment can be produced by forming a coating layer containing a curable resin on the base film 2, giving a concavo-convex shape to the surface of the coating layer, and then curing the coating layer. Figure 2 It is a figure which shows the manufacturing method of the anti-glare film 1 of 3rd Embodiment. Figure 2 In the example, an ultraviolet curing resin is used as the curable resin.
[0133] like Figure 2 As shown, in this manufacturing method, the base film 2 is unwound from a unwinding roll (not shown) and conveyed in a predetermined direction. The downstream end of the base film 2 in the conveying direction is inserted into and passes through the nip point N1 of a pair of rollers 21 and 22 .
[0134] The ultraviolet curable resin precursor is attached to the peripheral surface of the roller 22 by the peripheral surface of the roller 23 axially supported adjacent to the roller 22. The ultraviolet curable resin precursor is applied to one side of the base film 2 when the base film 2 passes through the nip point N1.
[0135] The layer of the ultraviolet curable resin precursor applied to the base film 2 (hereinafter referred to as the coating layer) is squeezed together with the base film 2 at the nip point of the rollers 21 and 24. The roller 24 is a roller-shaped mold (embossing roller) with fine concavoconvex shapes formed on the circumferential surface, and when passing through the nip point N2 between the rollers 21 and 24, the concavoconvex shapes are transferred to the surface of the coating layer.
[0136] The coating layer having the concavo-convex shape transferred to the surface by the roller 24 can be cured by ultraviolet rays irradiated by the ultraviolet lamp 26 provided below the rollers 21 and 24. Thus, the antiglare layer 3 of the antiglare film 1 of the third embodiment can be formed. The antiglare film 1 of the third embodiment manufactured in this way is released from the roller 24 by the roller 25 axially supported adjacent to the roller 24 and conveyed in a predetermined direction.
[0137] Here, the concavoconvex portions on the surface of the roller 24 are formed by blasting particles having a predetermined particle size by blasting. By adjusting the blasting particle size, the concavoconvex shape formed on the coating layer of the anti-glare film 1 can be adjusted.
[0138] As the base film 2 of the antiglare film 1 of the third embodiment, PET (polyethylene terephthalate) film, TAC (cellulose triacetate) film, COP (cycloolefin polymer) film, acrylic resin film, and polycarbonate resin film can be preferably used.
[0139] Thus, the preparation method of the anti-glare film 1 of the third embodiment includes the following steps: a step (a) of coating a curable resin precursor on a substrate film 2; a step (b) of preparing a roller-shaped mold having a concave-convex shape on a surface by hitting the sprayed particles; a step (c) of transferring the concave-convex shape to the surface of the curable resin precursor coated on the substrate film 2 using the roller-shaped mold; and a step (d) of curing the curable resin precursor to which the concave-convex shape was transferred to form an anti-glare layer 3 having a concave-convex shape on a surface.
[0140] The average particle size of the sprayed particles used in step (b) can be appropriately set, but as an example, it can be set to a value in the range of 10 μm or more and 50 μm or less. The average particle size of the sprayed particles is further preferably a value in the range of 20 μm or more and 45 μm or less, and more preferably a value in the range of 30 μm or more and 40 μm or less. Thus, the anti-glare layer 3 of the third embodiment with a concavo-convex shape on the surface can be obtained.
[0141] It should be noted that the mold used in the third embodiment can be a plate-shaped mold (embossed plate) in addition to a roll-shaped mold. In addition, after forming a coating (resin layer) on one side of the substrate film 2 of the third embodiment, the surface of the coating can be shaped by the mold to form the anti-glare layer 3 of the third embodiment. In addition, in the above example, the coating is cured after the surface of the coating is shaped, but the coating can also be shaped and cured at the same time.
[0142] As for the material of the mold, as an example, metal, plastic, and wood can be cited. On the contact surface of the mold with the coating, in order to improve the durability (wear resistance) of the mold, a film can be provided. As an example, the material of the sprayed particles can be cited as metal, silicon dioxide, aluminum oxide, and glass. The sprayed particles can, for example, hit the surface of the mold by the pressure of gas or liquid. In addition, if the curing resin precursor is an electron beam curing type, an electron beam source such as an electron beam accelerator can be used instead of the ultraviolet lamp 26, and if it is thermosetting, a heating source such as a heater can be used instead of the ultraviolet lamp 26.
[0143] It should be noted that the anti-glare layer 3 of the anti-glare film 1 of each embodiment described above may further include an upper layer disposed on the surface opposite to the substrate film 2. By providing the upper layer, the external haze of the anti-glare layer 3 can be easily adjusted, and the anti-glare film 1 can be easily protected from the outside.
[0144] The thickness of the upper layer can be appropriately set, for example, to a value in the range of 10 nm to 2.0 μm. The thickness of the upper layer is more preferably in the range of 50 nm to 1.0 μm, and further preferably in the range of 70 nm to 0.5 μm.
[0145] Next, refer to Figure 3 An evaluation device and an evaluation method for quantitatively evaluating the glare of the anti-glare film 1 according to each of the above-described embodiments will be described.
[0146] (Glare inspection machine)
[0147] Figure 3 1 is a diagram showing an example of a schematic structure of a glare inspection machine 10 according to an embodiment of the present invention. The glare inspection machine 10 is a device for inspecting the size of glare on a display 16a of a display device 16 equipped with an anti-glare film 1. The glare inspection machine 10 includes a housing 11, a camera 12, a holding portion (adjustment portion) 13, a camera bracket 14, a display bracket (adjustment portion) 15, and an image processing device 17.
[0148] The housing 11 is a part for forming a darkroom as an inspection space for glare evaluation, and is formed in a hollow rectangular parallelepiped shape. The housing 11 contains: a camera 12, a holding portion 13, a camera bracket 14, a display bracket 15, and a display device 16 to be the object of glare evaluation. It should be noted that the housing 11 is formed to prevent light from entering the housing 11 from the outside when the camera 12 is used for shooting.
[0149] As an example, the camera 12 is an area camera having a lens 18 and a camera element, and captures an image displayed on the display 16a. The camera 12 is held by the holding portion 13 in such a manner that the lens 18 faces the display 16a. The camera 12 is connected to the image processing device 17, and image data captured by the camera 12 is sent to the image processing device 17.
[0150] The holding portion 13 is arranged along the vertical direction ( Figure 3 The base end side of the holding part 13 is fixed by the camera bracket 14, and the camera 12 is held at the front end side. The camera 12 can be moved in the vertical direction by the holding part 13, and the relative distance between the display 16a and the lens 18 can be changed.
[0151] The display device 16 is placed on the display device support 15 in a state where the display 16a with the anti-glare film 1 is opposite to the camera 12. The display device support 15 supports the display device 16 in a manner that the surface of the display 16a with the anti-glare film 1 is opposite to the camera 12 and forms a horizontal plane, and moves the display device 16 in the vertical direction to change the relative distance between the display 16a and the lens 18.
[0152] In the glare inspection machine 10, the size of the image displayed on the display 16a photographed by the imaging element of the imaging device 12 is adjusted by adjusting the relative distance between the imaging device 12 and the display 16a. In other words, the pixel size of the image photographed per unit pixel (e.g., 1 pixel) of the imaging element of the imaging device 12 and displayed on the display 16a can be adjusted.
[0153] The image processing device 17 performs data processing on the image data captured by the image capturing device 12. Specifically, the image processing device 17 obtains the value of the standard deviation of the brightness of the image displayed on the display 16a based on the image data captured by the image capturing device 12.
[0154] The image processing device 17 of this embodiment includes: an input unit for inputting image data captured by the imaging device 12, an image processing unit for performing image processing on the input image data, and an output unit for outputting the result processed by the image processing unit to a display or printing device (not shown).
[0155] It should be noted that the method of adjusting the pixel size of the image captured by each unit pixel (for example, 1 pixel) of the imaging element and displayed on the display 16a can be, in addition to the method of changing the relative distance between the imaging device 12 and the display 16a, a method of changing the focal length of the imaging device 12 when the lens 18 of the imaging device 12 is a zoom lens.
[0156] (Evaluation method for glare)
[0157] Next, a glare evaluation method using the glare inspection device 10 is described. In this glare evaluation method, for the sake of evaluation, the display 16a with the anti-glare film 1 mounted on the surface is uniformly illuminated in a single color (green as an example) in advance for display.
[0158] First, the pixel size of the display 16 a mounted with the anti-glare film 1 captured per unit pixel of the imaging element of the imaging device 12 is adjusted to a given value (adjustment step).
[0159] In the adjustment step, the relative distance between the shooting device 12 and the display 16a equipped with the anti-glare film 1 is adjusted according to the effective pixel number of the shooting element of the shooting device 12, and is adjusted to a level where there are no bright lines of pixels of the image displayed by the display 16a equipped with the anti-glare film 1 in the image data captured by the shooting device 12, or even if there are bright lines, it will not affect the evaluation of glare.
[0160] It should be noted that the relative distance between the camera 12 and the display device 16 is preferably set in consideration of the actual usage of the display device 16 (eg, the relative distance between the user's eyes and the display 16 a ).
[0161] After the adjustment step, a measurement area for evaluating the glare of the display 16a equipped with the anti-glare film 1 is set (setting step). In the setting step, the measurement area can be appropriately set according to the size of the display 16a, for example.
[0162] After the adjustment step, the measurement area of the display 16a equipped with the anti-glare film 1 is photographed by the photographing device 12 (photographing step). At this time, as an example, at least one of the exposure time of the photographing device 12 or the brightness of all pixels of the display 16a is adjusted to obtain image data of a grayscale image with an 8-bit grayscale display and an average brightness of 170 grayscales. The image data obtained in the photographing step is input to the image processing device 17.
[0163] After the shooting step, the image processing device 17 obtains the brightness unevenness in the image of the measurement area of the display 16a equipped with the anti-glare film 1 through the image data (calculation step). In this calculation step, the brightness unevenness can be quantified by obtaining the standard deviation of the brightness distribution. Here, the greater the brightness unevenness of the display 16a equipped with the anti-glare film 1, the greater the glare degree of the display 16a equipped with the anti-glare film 1. Based on this, the smaller the value of the standard deviation of the brightness distribution, the more it can be quantitatively and objectively evaluated as less glaring. In addition, since the bright line of the display 16a equipped with the anti-glare film 1 is adjusted to a degree that does not affect the evaluation of glare in the adjustment step, it is possible to suppress the brightness unevenness caused by the bright line and perform an accurate glare evaluation.
[0164] By going through the above steps, the standard deviation of the brightness distribution of the display 16 a with the anti-glare film 1 mounted on the surface can be obtained, and the glare can be evaluated based on the magnitude of the value.
[0165] (Examples and Comparative Examples)
[0166] Hereinafter, the present invention will be described in more detail based on examples, but the present invention is not limited to these examples.
[0167] Examples 1 to 5 are examples of anti-glare films 1 produced by the phase separation method and satisfying the following conditions: the glare value is 10 or less, the specular glossiness (60-degree glossiness) is 40% or less, and the transmission image clarity (image clarity) at a comb width of 0.5 mm is 40% or less. In other words, Examples 1 to 5 are examples of anti-glare films 1 that can satisfy the above conditions based on the concavo-convex shape formed on the surface of the anti-glare film 1 by the phase separation method.
[0168] Example 6 is an example of an anti-glare film 1 produced by a particle dispersion method and satisfying the following conditions: the glare value is less than 10, the mirror glossiness (60 degree glossiness) is less than 40%, and the transmission image clarity (image clarity) with a comb width of 0.5 mm is less than 40%.
[0169] On the other hand, Comparative Examples 1 to 3 are examples of the anti-glare film 1 produced by the fine particle dispersion method, and Comparative Examples 4 and 5 are examples of the anti-glare film 1 produced by the transfer formation method.
[0170] [raw material]
[0171] The following materials were used as the raw materials in Examples and Comparative Examples. In addition, the refractive index described below means the refractive index after crosslinking (after curing) for materials cured by crosslinking.
[0172] Acrylic polymer A having a polymerizable group: [CYCLOMER P] manufactured by Daicel Allnex Corporation (refractive index: 1.51)
[0173] Cellulose acetate propionate: [CAP-482-20] manufactured by Eastman Co., Ltd. (refractive index: 1.49), degree of acetylation = 2.5%, degree of propionylation = 46%, number average molecular weight in terms of polystyrene: 75,000
[0174] Acrylic UV-curable compound containing nano-silica (refractive index 1.46): MOMENTIVE PERFORMANCE MATERIALS JAPAN Co., Ltd. [UVHC7800G] (refractive index 1.52)
[0175] Silicone acrylate: [EB1360] manufactured by Daicelallnex Corporation (refractive index 1.52)
[0176] Urethane acrylate: [UA-53H] manufactured by Shin-Nakamura Chemical Co., Ltd. (refractive index 1.52)
[0177] Dipentaerythritol hexaacrylate: [DPHA] manufactured by Daicelallnex Corporation (refractive index 1.52)
[0178] Pentaerythritol tetraacrylate: [PETRA] manufactured by Daicelallnex Corporation (refractive index 1.52)
[0179] Acrylic ultraviolet curable compound containing silica (refractive index 1.46): [Z-757-4RL] manufactured by AICA Industries, Ltd. (refractive index 1.52)
[0180] Fluorine compound with polymerizable group: Fluorine antifouling additive [KY-1203] manufactured by Shin-Etsu Chemical Co., Ltd.
[0181] Alkyl phenone-based photopolymerization initiator (photopolymerization initiator A): manufactured by BASF [IRGACURE 184]
[0182] Alkyl phenone-based photopolymerization initiator (photopolymerization initiator B): BASF [IRGACURE 907]
[0183] Polyethylene terephthalate (PET) film: Made by Mitsubishi Plastics Corporation [DIAFOIL]
[0184] Triacetyl cellulose (TAC) film: manufactured by FUJIFILM Corporation [FUJITAC TG60UL]
[0185] [Example 1]
[0186] A solvent was prepared by dissolving 50 parts by mass of an acrylic polymer having a polymerizable group, 4 parts by mass of cellulose acetate propionate, 76 parts by mass of urethane acrylate, 1 part by mass of silicone acrylate, 1 part by mass of photopolymerization initiator A, and 1 part by mass of photopolymerization initiator B in a mixed solvent of 176 parts by mass of methyl ethyl ketone and 28 parts by mass of 1-butanol.
[0187] The solution was cast on a PET film (substrate film 2) using a wire rod (#18), and then placed in an oven at 80°C for 1 minute to evaporate the solvent and form a coating with a thickness of about 9 μm. Then, the coating was irradiated with ultraviolet light for about 5 seconds using an ultraviolet lamp such as a high-pressure mercury lamp to perform ultraviolet curing on the coating. Thus, an anti-glare layer 3 was formed, and the anti-glare film of Example 1 was obtained.
[0188] [Example 2]
[0189] A solvent was prepared by dissolving 50 parts by mass of an acrylic polymer having a polymerizable group, 4 parts by mass of cellulose acetate propionate, 76 parts by mass of urethane acrylate, 1 part by mass of silicone acrylate, 1 part by mass of a fluorine compound having a polymerizable group, 1 part by mass of a photopolymerization initiator A, and 1 part by mass of a photopolymerization initiator B in a mixed solvent of 176 parts by mass of methyl ethyl ketone and 28 parts by mass of 1-butanol.
[0190] The solution was cast on a PET film (substrate film 2) using a wire rod (#14), and then placed in an oven at 80°C for 1 minute to evaporate the solvent and form a coating with a thickness of about 6 μm. Then, the coating was irradiated with ultraviolet light for about 5 seconds using an ultraviolet lamp to perform ultraviolet curing on the coating. Thus, an anti-glare layer 3 was formed, and an anti-glare film of Example 2 was obtained.
[0191] [Example 3]
[0192] A solvent was prepared by dissolving 12.5 parts by mass of an acrylic polymer having a polymerizable group, 4 parts by mass of cellulose acetate propionate, 150 parts by mass of an acrylic ultraviolet curable compound containing nanosilica, 1 part by mass of silicone acrylate, 1 part by mass of photopolymerization initiator A, and 1 part by mass of photopolymerization initiator B in a mixed solvent of 81 parts by mass of methyl ethyl ketone, 24 parts by mass of 1-butanol, and 13 parts by mass of 1-methoxy-2-propanol.
[0193] The solution was cast on a PET film (substrate film 2) using a wire rod (#20), and then placed in an oven at 80°C for 1 minute to evaporate the solvent and form a coating layer with a thickness of about 9 μm. Then, the coating layer was irradiated with ultraviolet light for about 5 seconds using an ultraviolet lamp to perform ultraviolet curing treatment, thereby forming an anti-glare layer 3, and an anti-glare film of Example 3 was obtained.
[0194] [Example 4]
[0195] A solvent was prepared by dissolving 15.0 parts by mass of an acrylic polymer having a polymerizable group, 3 parts by mass of cellulose acetate propionate, 150 parts by mass of an acrylic ultraviolet curable compound containing nanosilica, 1 part by mass of silicone acrylate, 1 part by mass of photopolymerization initiator A, and 1 part by mass of photopolymerization initiator B in a mixed solvent of 101 parts by mass of methyl ethyl ketone and 24 parts by mass of 1-butanol.
[0196] The solution was cast on a PET film (substrate film 2) using a wire rod (#20), and then placed in an oven at 80°C for 1 minute to evaporate the solvent and form a coating layer with a thickness of about 9 μm. Then, the coating layer was irradiated with ultraviolet light for about 5 seconds using an ultraviolet lamp to perform ultraviolet curing treatment, thereby forming an anti-glare layer 3, and an anti-glare film of Example 4 was obtained.
[0197] [Example 5]
[0198] A solvent was prepared by dissolving 50 parts by mass of an acrylic polymer having a polymerizable group, 2.5 parts by mass of cellulose acetate propionate, 79.5 parts by mass of urethane acrylate, 1 part by mass of silicone acrylate, 1 part by mass of photopolymerization initiator A, and 1 part by mass of photopolymerization initiator B in a mixed solvent of 106 parts by mass of methyl ethyl ketone, 28 parts by mass of 1-butanol, and 70 parts by mass of cyclohexanone.
[0199] The solution was cast on a PET film (substrate film 2) using a wire rod (#12), and then placed in an oven at 80°C for 1 minute to evaporate the solvent and form a coating layer with a thickness of about 5 μm. Then, the coating layer was irradiated with ultraviolet light for about 5 seconds using an ultraviolet lamp to perform ultraviolet curing treatment, thereby forming an anti-glare layer 3, and an anti-glare film of Example 4 was obtained.
[0200] [Example 6]
[0201] A mixed solvent of 50 parts by mass of an acrylic ultraviolet curable compound (refractive index: 1.52) containing silica (refractive index: 1.46) and 50 parts by mass of 1-butanol was prepared.
[0202] The solution was cast on a PET film (substrate film 2) using a wire rod (#16), and then placed in an oven at 80°C for 1 minute to evaporate the solvent and form a coating with a thickness of about 7 μm. Then, the coating was irradiated with ultraviolet light for about 5 seconds by an ultraviolet lamp to perform ultraviolet curing treatment, thereby forming an anti-glare layer 3, and an anti-glare film of Example 6 was obtained. It should be noted that when the weight of the matrix resin (acrylic ultraviolet curable compound) is set to G1 and the weight of the microparticles (silicon dioxide) contained in the anti-glare layer 3 is set to G2, the ratio of the two G2 / G1 is 0.14.
[0203] [Comparative Example 1]
[0204] As a transparent substrate, triacetyl cellulose (manufactured by FUJIFILM Corporation, thickness 80 μm) was prepared.
[0205] Pentaerythritol triacrylate (PETA; manufactured by Daicel Allnex Co., Ltd., refractive index 1.51) was used as a transparent resin, and styrene-acrylic copolymer particles (refractive index 1.51, average particle size 9.0 μm) and polystyrene particles (refractive index 1.60, average particle size 3.5 μm) as light-transmitting particles were contained in an amount of 10.0 parts by mass and 16.5 parts by mass, respectively, relative to 100 parts by mass of the transparent resin. A mixed solvent (mass ratio 7:3) of toluene (boiling point 110° C.) and cyclohexanone (boiling point 156° C.) was mixed therein in an amount of 190 parts by mass relative to 100 parts by mass of the transparent resin to obtain a resin composition.
[0206] The resin composition was coated on a transparent substrate, and dried for 1 minute with dry air at 85°C at a flow rate of 1 m / s. The coating thickness was set to 5 μm. Then, ultraviolet light was irradiated using an ultraviolet lamp (200 / cm in a nitrogen atmosphere). 2 ) and the transparent resin is subjected to ultraviolet curing treatment to form an anti-glare layer 3, thereby obtaining the anti-glare film of Comparative Example 1.
[0207] [Comparative Example 2]
[0208] As a transparent substrate, triacetyl cellulose (manufactured by FUJIFILM Corporation, thickness 80 μm) was prepared.
[0209] As a transparent resin, a mixture (mass ratio; PETA / DPHA / PMMA=86 / 5 / 9) (refractive index 1.51) of pentaerythritol triacrylate (PETA; manufactured by Daicel Allnex Co., Ltd.), dipentaerythritol hexaacrylate (DPHA; manufactured by Daicel Allnex Co., Ltd.), and polymethyl methacrylate (BR85; manufactured by Mitsubishi Rayon) was used, and polystyrene particles (refractive index 1.60, average particle size 3.5 μm) and styrene-acrylic copolymer particles (refractive index 1.56, average particle size 3.5 μm) as light-transmitting particles were contained in an amount of 18.5 parts by mass and 3.5 parts by mass, respectively, relative to 100 parts by mass of the transparent resin. A mixed solvent (mass ratio 7:3) of toluene (boiling point 110° C.) and cyclohexanone (boiling point 156° C.) was mixed therein in an amount of 190 parts by mass relative to 100 parts by mass of the transparent resin to obtain a resin composition.
[0210] The resin composition was coated on a transparent substrate, and dried for 1 minute with dry air at 70°C at a flow rate of 0.2 m / s. The coating thickness was set to 3.5 μm. Then, ultraviolet light was irradiated using an ultraviolet lamp (200 mJ / cm in a nitrogen atmosphere). 2 ) and the transparent resin is subjected to ultraviolet curing treatment to form an anti-glare layer 3, thereby obtaining an anti-glare film of Comparative Example 2.
[0211] [Comparative Example 3]
[0212] As a transparent substrate, triacetyl cellulose (manufactured by FUJIFILM Corporation, thickness 80 μm) was prepared.
[0213] Pentaerythritol triacrylate (PE-3A; manufactured by Kyoeisha Chemical, refractive index 1.53) was used as a transparent resin, and silica particles (SS50F; manufactured by TOSOH-SILICA Industries, refractive index 1.47, average particle size 1.1 μm) and polystyrene particles (refractive index 1.59, average particle size 3.5 μm) as light-transmitting particles were contained in an amount of 26 parts by mass and 6.6 parts by mass, respectively, relative to 100 parts by mass of the transparent resin. 5.3 parts by mass of a photopolymerization initiator A and 138 parts by mass of toluene (boiling point 110° C.) as a solvent were mixed therein to obtain a resin composition.
[0214] The resin composition was coated on a transparent substrate, and dried for 1 minute with dry air at 90°C at a flow rate of 0.2 m / s. The coating thickness was set to 5 μm. Then, ultraviolet light was irradiated using an ultraviolet lamp (200 mJ / cm in a nitrogen atmosphere). 2 ) and the transparent resin is subjected to ultraviolet curing treatment to form an anti-glare layer 3, thereby obtaining an anti-glare film of Comparative Example 3.
[0215] [Comparative Examples 4 and 5]
[0216] The anti-glare films of Comparative Examples 4 and 5 were produced by forming a coating layer made of ultraviolet curing resin on a substrate film, on which the unevenness was transferred using a mold. The production process of the anti-glare film using the transfer molding method has been described above, so its detailed description is omitted.
[0217] That is, the method for preparing the anti-glare film of Comparative Examples 4 and 5 includes: a step (a) of coating a UV-curable resin precursor on a substrate film; a step (b) of making a roller-shaped mold having a concave-convex shape on a surface by hitting the sprayed particles; a step (c) of transferring the concave-convex shape to the surface of the UV-curable resin precursor coated on the substrate film using the roller-shaped mold; and a step (d) of irradiating the UV-curable resin precursor to which the concave-convex shape has been transferred with ultraviolet rays to cure it and form a coating layer having a concave-convex shape on the surface.
[0218] In step (b), a roll-shaped mold having a spray particle size varying in the range of 10 μm to 40 μm was prepared, and two films (Comparative Examples 4 and 5) having different haze (Hz) values were prepared by the above-mentioned production method.
[0219] In addition, in Comparative Examples 4 and 5, a TAC (triacetyl cellulose) film can be preferably used as the base film.
[0220] In addition, each anti-glare film of Examples 1 to 6 and Comparative Examples 1 to 5 was evaluated by measuring the following items.
[0221] [Haze and total light transmittance]
[0222] The haze was measured using a haze meter (NDH-5000W manufactured by Nippon Denshoku Co., Ltd.) in accordance with JIS K 7136. The haze was measured by placing the surface having the concavo-convex structure on the light receiving side.
[0223] [Transmission image clarity]
[0224] The image clarity meter (ICM-1T manufactured by SUGA TEST INSTRUMENTS Co., Ltd.) was used to measure the anti-glare film in accordance with JIS K 7105, with the film forming direction of the anti-glare film being parallel to the direction of the comb teeth of the optical comb. The optical comb width was 0.5 mm.
[0225] [60 degree glossiness]
[0226] The glossiness was measured at an angle of 60° using a gloss meter (IG-320, manufactured by Horiba, Ltd.) in accordance with JIS K7105.
[0227] [Standard deviation of display brightness distribution (glare value)]
[0228] As the display device 16, a smartphone (Galaxy S4 manufactured by Samsung Electronics Co., Ltd.) was used, and the anti-glare film of each sample was attached to the surface of its display 16a by optical paste. It should be noted that the resolution of the display 16a of the smartphone is 441ppi. Then, using a glare inspection machine 10 manufactured by KOMATSU NTC Co., Ltd., the standard deviation (glare value) of the brightness distribution of the display 16a was measured via the anti-glare film of each sample. During the measurement, at least one of the exposure time of the camera 12 or the brightness of all pixels of the display 16a was adjusted to obtain image data of a grayscale image with an 8-bit grayscale display and an average brightness of 170 grayscales.
[0229] Here, Table 1 shows the measurement results of each of the above items.
[0230]
[0231] As shown in Table 1, an anti-glare film that meets the above conditions (glare value of less than 10, mirror gloss of less than 40%, and transmitted image clarity of less than 40%) can be obtained by a phase separation method based on the raw materials and production conditions of Examples 1 to 5, and a particle dispersion method based on the raw materials and production conditions of Example 6.
[0232] That is, it can be seen that by setting the type of phase separation material combined, the heating temperature of the composition in the drying process, the air volume of the dry air blown to the composition, or the linear speed, etc. as in Examples 1 to 5, a concave-convex shape that satisfies the above conditions can be formed on the surface of the anti-glare film 1.
[0233] It is also known that the anti-glare film 1 satisfying the above conditions can be formed by selecting the particles dispersed in the matrix resin so that the difference in refractive index between the particles and the matrix resin is within a range of 0 or more and 0.07 or less, and by making the ratio G2 / G1 of the weight G1 of the matrix resin to the total weight G2 of the plurality of particles contained in the anti-glare layer reach 0.03 to 0.20, and by making the film under the production conditions shown in Example 6. That is, it is believed that in the particle dispersion method of Example 6, by selecting materials when forming the anti-glare layer 3, the repulsive interaction between the particles and the resin and solvent other than the particles is enhanced, and the particles can be appropriately aggregated, so that a steep and high-density concave-convex distribution structure can be formed in the anti-glare layer 3.
[0234] On the other hand, the anti-glare film satisfying the above conditions could not be produced by the particle dispersion method based on the raw materials and production conditions of Comparative Examples 1 to 3. That is, in Comparative Examples 1 and 2, the difference in refractive index between the particles and the matrix resin was greater than 0.07. In Comparative Example 3, the ratio G2 / G1 of the weight G1 of the matrix resin to the total weight G2 of the plurality of particles contained in the anti-glare layer was not within the range of 0.03 or more and 0.20 or less.
[0235] Furthermore, the transfer molding method based on the raw materials and production conditions of Comparative Examples 4 and 5 could not form a statistically controllable concavoconvex shape on the antiglare film as in the phase separation method of Examples 1 to 3, and an antiglare film satisfying the above conditions could not be produced.
[0236] The present invention is not limited to the above-mentioned embodiment, and within the scope of not departing from the gist of the present invention, its formation or method can be changed, added or deleted. For example, the microparticles of the second embodiment can also be dispersed in the matrix resin of the anti-glare layer 3 of the first embodiment or the 3rd embodiment.
Claims
1. An anti-glare film installed on the surface of a display. in, The anti-glare film comprises an anti-glare layer. The glare value of the anti-glare layer is a value in the range of 4.5 to 9.5, the glare value being a value defined based on a value of a standard deviation of brightness distribution of the organic EL display when the anti-glare layer is mounted on the surface of the organic EL display having a pixel density of 441 ppi and image data is obtained as an 8-bit grayscale display with an average brightness of 170 grayscales, The anti-glare layer has a transmission image clarity of 2.9% to 40% at a light comb width of 0.5 mm, and a haze value of 31.4% to 79.5%. The anti-glare layer includes a matrix resin and a plurality of fine particles dispersed in the matrix resin and having an average particle size in a range of 0.5 μm to 5.0 μm.
2. The anti-glare film according to claim 1, wherein: The anti-glare layer includes a plurality of resin components and has a co-continuous phase structure formed by phase separation of the plurality of resin components.
3. The anti-glare film according to claim 1, wherein: The difference in refractive index between the fine particles and the matrix resin is a value in a range of 0 to 0.
07.
4. The anti-glare film according to claim 3, wherein: A ratio G2 / G1 of a weight G1 of the base resin of the anti-glare layer to a total weight G2 of the plurality of fine particles included in the anti-glare layer is a value in a range of 0.03 to 0.20.
Citation Information
Patent Citations
Light diffusion sheet
JP2009109702A
Pilot signal-based transmission power control
JP2012231496A
Optical film and production method of the same
JP2014102356A
Hard-coated antiglare film, polarizing plate, and image display
CN101074996A
Antiglare film
JP2012133066A